Hollow dodecahedral Co3S4@NiO derived from ZIF-67 for supercapacitor. (1st May 2020) - Hou, Shuangyue; Lian, Yue; Bai, Yongqing; Zhou, Qiuping; Ban, Chaolei; Wang, Zhifeng; Zhao, Jing; Zhang, Huaihao
Abstract: Transition metal sulfide is considered a promising electrode material for supercapacitors because of its high theoretical specific capacitance and good redox reversibility. However, it is difficult for a single material to deliver ideal specific capacity and cycling stability. Herein, we report a rhombohedral dodecahedral composite Co3 S4 @NiO for supercapacitor. This heterogeneous hollow structure of Co3 S4 @NiO exposes more active sites, promotes free diffusion of electrolytes, shortens the path of electron transfer in electrochemical reaction process, and improves the capacitance performance. The electrochemical test results show its specific capacitance up to 1877.93 F g −1 in 6 M KOH electrolyte at the specific current 1 A g −1 . In particular, the composite exhibits good cyclic stability with 92.6% capacity retention after 10, 000 cycles at the specific current 5 A g −1 . Meanwhile, the asymmetric supercapacitors, assembled with Co3 S4 @NiO as positive electrode and activated carbon as negative electrode, delivered high energy density 54.99 Wh kg −1 as for the power density 0.78 kW kg −1, also proving its high capacitance performance of Co3 S4 @NiO with unique structure. Highlights: The hollow polyhedral complex Co3 S4 @NiO was successfully synthesized by a facile method. The Co3 S4 @NiO achieves remarkable specific capacitance of 1877.93 F g −1 at 1 A g −1 . The Co3 S4 @NiO exhibits an excellent cycling stability (92.6% for 10, 000 cycles). The Co3 S4 @NiO//AC display high energy density of 54.99 Wh kg −1 at a power density of 0.78 kW kg −1 .